MALDI-MS: a Rapid and Reliable Method for Drug-to-Antibody Ratio Determination of Antibody-Drug Conjugates - Abedi, Mehri (Iran Biomed J, 2019)
BACKGROUND: It is believed that the loading value of anticancer drug conjugated to the monoclonal antibody, called drug-to-antibody ratio (DAR), is the main quality feature of antibody-drug conjugates. METHODS: In this study, matrix assisted laser desorption/ionization mass spectrometry was used to determine the average molecular weight of trastuzumab and its three conjugated forms. The differences in the measured masses for each conjugate and unconjugated trastuzumab were compared to the expected mass change through the conjugation of one mole of related drug-linker, in order to measure DAR. RESULTS: There was a consistency between the loading results of mass spectrometry and the measurements of UV spectrometry in most cases. Conclusion: According to our findings, the MALDI-MS method for determining the loading values can be used rapidly and reliably to estimate the covalently bound drugs conjugated to antibodies when ESI-TOF-MS is unavailable.